2018 IEEE Information Theory Workshop (ITW) 2018
DOI: 10.1109/itw.2018.8613428
|View full text |Cite
|
Sign up to set email alerts
|

Binary Linear Codes with Optimal Scaling: Polar Codes with Large Kernels

Abstract: We prove that, at least for the binary erasure channel, the polar-coding paradigm gives rise to codes that not only approach the Shannon limit but, in fact, do so under the best possible scaling of their block length as a function of the gap to capacity. This result exhibits the first known family of binary codes that attain both optimal scaling and quasi-linear complexity of encoding and decoding. Specifically, for any fixed δ > 0, we exhibit binary linear codes that ensure reliable communication at rates wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(67 citation statements)
references
References 40 publications
2
65
0
Order By: Relevance
“…Now it remains to find the explicit constructions of such optimal kernels. Our results in this paper can be viewed as another step towards the derandomization of the proof in [3].…”
Section: Related Prior Workmentioning
confidence: 91%
See 1 more Smart Citation
“…Now it remains to find the explicit constructions of such optimal kernels. Our results in this paper can be viewed as another step towards the derandomization of the proof in [3].…”
Section: Related Prior Workmentioning
confidence: 91%
“…Attempts to achieve the optimal scaling exponent of 2 were first seen in [10], where it was shown that polar codes can achieve the near-optimal scaling exponent of µ = 2 + ǫ by using explicit large kernels over large alphabets. The conjecture was just recently solved in [3], where it was shown that one can achieve the near-optimal scaling exponent via almost any binary ℓ × ℓ kernel given that ℓ is sufficiently large enough. Now it remains to find the explicit constructions of such optimal kernels.…”
Section: Related Prior Workmentioning
confidence: 99%
“…where α 1 and α 2 are positive constants depending on P e and I(W ). It is known from [4] that scaling exponent for random codes equals 2 and shown in [5] that µ for polar codes approaches 2 as l → ∞ with high probability for BEC channel over random choice of the kernel. It is already known that µ = 3.627 for conventional polar codes (Arikans T 2 kernel) over BEC [5].…”
Section: A Scaling Exponentmentioning
confidence: 99%
“…It is known from [4] that scaling exponent for random codes equals 2 and shown in [5] that µ for polar codes approaches 2 as l → ∞ with high probability for BEC channel over random choice of the kernel. It is already known that µ = 3.627 for conventional polar codes (Arikans T 2 kernel) over BEC [5]. Recently, a class of self-dual binary kernels were introduced in [6] in which large kernels of size 2 p were constructed with low µ and it was shown that µ = 3.122 for L = 32 and µ 2.87 for L = 64.…”
Section: A Scaling Exponentmentioning
confidence: 99%
“…Finally, these values are used in (13) 3) phase 5: The decoding window D 5 remains the same as in the previous phase. According to expressions (7) and (8) Once the value u 6 is determined, one can obtain S 1,7 with one operation directly from already computed values max v 10 0 ∈Z 7,b R(v 10 0 |y 15 0 ). 6) phase 8: At this phase the decoding window is increased and given by D 8 = {5, 6, 7, 11} and h 8 = 12.…”
Section: Instead Of Exhaustive Enumeration Of Vectors Vmentioning
confidence: 99%